Perancangan Aplikasi Quiz Interaktif Bahasa Inggris dengan Metode Convolutional Neural Network (CNN) menggunakan Macromedia Flash 8 - Riza Rahmadani; Mufida Khairani; Siti Sundari (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
This research is a research on the development of learning media based on macromedia flash 8 in English quiz lessons for elementary students. This study aims to foster the interest of grade 2 elementary school students to usecomputers as learning media, create an interactive English quiz program to help increase the motivation andunderstanding of grade 2 elementary school students in learning English and improve intelligence IQ (IntelligenceQoutient), EQ ( Emotional Qoutient) and SQ (Spiritual Qoutient) in children. The benefits of this research canadd insight or knowledge of children in terms of answering the questions given as learning, can train thedevelopment of elementary level children to better understand quizzes, can be used as learning media that attractschildren's talents, can increase children's intelligence about technology, and motivate children to learn English.The method used is Convolutional Neural Network (CNN). The results of this study indicate that a computer-basedEnglish quiz interactive learning application has been designed using macromedia flash 8 software, the design ofan English quiz interactive learning application consists of a display design for quiz questions and answers,English language material designed in the form of animated images, animated text, and an explanation of thematerial by including voices to make elementary school students enthusiastic about taking lessons, macromediaflash 8 as a means to present computer-based English learning, a learning application made to attract users'interest in receiving lessons and make it easier with interesting applications in the learning process teach.